2006
DOI: 10.1063/1.2221660
|View full text |Cite
|
Sign up to set email alerts
|

Implosion dynamics and radiative characteristics of a high yield structured gas puff load

Abstract: A large diameter gas puff nozzle, designed to produce a radial mass profile with a substantial fraction of the injected mass on the axis, has demonstrated an increase in K shell yield by nearly a factor of 2, to 21kJ, in an argon Z pinch at 3.5MA peak current and 205ns implosion time [H. Sze, J. Banister, B. H. Failor, J. S. Levine, N. Qi, A. L. Velikovich, J. Davis, D. Lojewski, and P. Sincerny, Phys. Rev. Lett. 95, 105001 (2005)] and 80kJ at 6MA and 227ns implosion time. The initial gas distribution produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…These measurements are consistent with the radiator-stabilizer-pusher model of the jet-innerouter gas puff described by Sze et al 1 in which the jet mass is heated and radiates in the K-shell, while the inner and outer shells remain cooler and produce much less K-shell radiation. Indeed, measurements of Cl dopant K-shell emission reported by Levine et al 2 indicate that most of the Ar K-shell emission is produced by mass that originated in the center jet ͑65%͒, followed by the inner shell ͑30%͒ and the outer shell ͑5%͒. Given the load mass distribution ͑center jet 20%, inner 40%, and outer 40%͒, the relative K-shell yield per unit mass for the inner and outer were only 23% and 4%, respectively, compared to the center jet.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These measurements are consistent with the radiator-stabilizer-pusher model of the jet-innerouter gas puff described by Sze et al 1 in which the jet mass is heated and radiates in the K-shell, while the inner and outer shells remain cooler and produce much less K-shell radiation. Indeed, measurements of Cl dopant K-shell emission reported by Levine et al 2 indicate that most of the Ar K-shell emission is produced by mass that originated in the center jet ͑65%͒, followed by the inner shell ͑30%͒ and the outer shell ͑5%͒. Given the load mass distribution ͑center jet 20%, inner 40%, and outer 40%͒, the relative K-shell yield per unit mass for the inner and outer were only 23% and 4%, respectively, compared to the center jet.…”
Section: Discussionmentioning
confidence: 95%
“…1 The factor of Ϸ2 difference between the hot core and cool blanket FWHM is consistent with the observed 25% K-shell-emitting mass fraction. 2 We have also observed that the XUV emission time history and its time integral are strong functions of the puff gas density and radial density profile. If the puff density is sufficiently high, the puff will not be as highly ionized before the onset of K-shell emission, and a sharp increase in XUV emission will be observed at that time due to strong photoheating of the cool outer blanket.…”
Section: Introductionmentioning
confidence: 91%
“…This technique has lead to the most powerful and efficient plasma radiation source presently available in the laboratory. [27][28][29] Similar experiments with deuterium gas-puff lead in 2007 on the Z accelerator in Sandia have produced 3.7 Â 10 13 DD neutrons (at 2.34 MeV). 30 This result is only comparable with the one very recently obtained on the National Ignition Facility at Livermore of 2.4 Â 10 15 DT neutrons.…”
Section: Introductionmentioning
confidence: 92%
“…We anticipate that adding a center gas jet will produce a more stable pinched plasma column. [26][27][28] The 12.5 lm Al wire had a mass line density of 3 lg/cm, which is comparable to the 10 lg/cm gas puff. Similar to the process in wire array Z-pinches, there was a solid Al core that did not participate in the implosion.…”
Section: B Ne/ar Implosions With a Wire On The Axismentioning
confidence: 97%